A Meta-analysis of Outcomes Using Acellular Dermal Matrix in Breast and Abdominal Wall Reconstructions: Event Rates and Risk Factors Predictive of Complications. Issue 2 (August 2016) - Adetayo, Oluwaseun A.; Salcedo, Samuel E.; Bahjri, Khaled; Gupta, Subhas C.
Abstract : Background: The use of acellular dermal matrix (ADM) has gained acceptance in breast and abdominal wall reconstructions. Despite its extensive use, there is currently a wide variation of reported outcomes in the literature. This study definitively elucidates the outcome rates associated with ADM use in breast and abdominal wall surgeries and identifies risk factors predisposing to the development of complications. Methods: A literature search was conducted using the Medline database (PubMed, US National Library of Medicine) and the Cochrane Library. A total of 464 articles were identified, of which 53 were eligible for meta-analysis. The endpoints of interest were the incidences of seroma, cellulitis, infection, wound dehiscence, implant failure, and hernia. The effects of various risk factors such as smoking, radiation, chemotherapy, and diabetes on the development of complications were also evaluated. Results: A majority of the studies were retrospective (68.6%) with a mean follow-up of 16.8 months (SD ± 10.1 months) in the breast group and 14.2 months (SD ± 7.8 months) in the abdominal wall reconstructive group. The overall risks and complications were as follows: cellulitis, 5.1%; implant failure, 5.9%; seroma formation, 8%; wound dehiscence, 8.1%; wound infection, 16.1%; hernia, 27.6%; and abdominal bulging, 28.1%. Complication rates were further stratified separately for the breast and abdominal cohorts, and the data were reported. This provides additional information on the associated abdominal wall morbidity in patients undergoing autologous breast reconstruction in which mesh reinforcement was considered as closure of the abdominal wall donor site. Radiation resulted in a significant increase in the rates of cellulitis ( P = 0.021), and chemotherapy was associated with a higher incidence of seroma ( P = 0.014). Conclusion: This study evaluates the overall complication rates associated with ADM use by conducting a meta-analysis of published data. This will offer physicians a single comprehensive source of information during informed consent discussions as well as an awareness of the risk factors predictive of complications.